Pengaruh Return On Investment, Economic Value Added Dan Market Value Added Terhadap Return Saham - Wahab, Dinda Illene; Handayani, Susi (Gorontalo Accounting Journal, 2023)
This study, which has a research period of 2019–2021, aims to determine the effect of Return on Investment (ROI), Economic Value Added (EVA) and Market Value Added (MVA) on stock returns in health sector companies and the telecommunications subsector listed on the Indonesia Stock Exchange. This study used a purposive sampling technique, which produced 99 data. Data analysis was carried out quantitatively and the hypothesis was tested by means of multiple regression analysis using SPSS version 26. The results of the analysis showed that simultaneously the variables ROI, EVA and MVA had an influence on stock returns. Meanwhile, partially, the results show that Return on Investment has a positive effect on stock returns, while Economic Value Added and Market Value Added have no effect on stock returns.